2014
DOI: 10.1016/j.gaitpost.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of foot muscles and plantar fascia in pes planus

Abstract: Greater CSA and thickness of the extrinsic muscles might reflect compensatory activity to support the MLA if the intrinsic foot muscle function has been compromised by altered foot structure. A thinner plantar fascia suggests reduced load bearing, and regional variations in structure and function in feet with pes planus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
133
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 29 publications
14
133
4
3
Order By: Relevance
“…Similar imbalances in the peroneal and anterior compartments of the leg muscles have been shown to contribute to cases of pes cavus associated with other pathologies [16]. Additionally, young adults with pes planus demonstrated different sizes and thicknesses of the intrinsic and extrinsic muscles of the foot on ultrasound compared with normal controls [42]. We found that greater overall muscle mass in the legs was associated with lower odds of pes cavus.…”
Section: Discussionsupporting
confidence: 70%
“…Similar imbalances in the peroneal and anterior compartments of the leg muscles have been shown to contribute to cases of pes cavus associated with other pathologies [16]. Additionally, young adults with pes planus demonstrated different sizes and thicknesses of the intrinsic and extrinsic muscles of the foot on ultrasound compared with normal controls [42]. We found that greater overall muscle mass in the legs was associated with lower odds of pes cavus.…”
Section: Discussionsupporting
confidence: 70%
“…This muscle weakness, however, was not evident at the ankle, as there were no significant differences in ankle dorsiflexion strength among the three participant groups. Intrinsic foot muscles such as the abductor hallucis, flexor hallucis brevis and flexor digitorum brevis make specific contributions to supporting the MLA [31] and have been found to be reduced in individuals with a lowered arch [32]. This reduced muscle strength may contribute to the increased foot pain evident in the obese participants, possibly due to an inability of the weaker foot muscles to maintain structural integrity of their feet.…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, the nature of kinematic variation between individuals may be such that assuming average population data represents normal function is invalid. Indeed sub classifications of symptom free feet into "cavus" and "planus" foot type do reveal differences in structure and function [32][33][34]. The mechanical (i.e.…”
Section: Discussionmentioning
confidence: 99%